PRINSIP, ASAS DAN KAIDAH HUKUM WARIS ISLAM ADIL GENDER (Jurnal Hukum Mimbar Justitia, 2017)
Theoretically, the Islamic inheritance law can be seen from different point of view basedon its object of law related to the division of property that has more dimension on civillaw and more closely within muamalah Fiqh as the scope of the study and related tointerpersonal law. Based on the writer's point of view, it is closer to the muamalahstudy which opens the possibility of ijtihad so that, Islamic law can be adapted in everyperiod of time. The problem of inheritance division assumed the concept of 'tribalism'and Islam comes to deconstruct the "tribalism" with the fundamental religion by theegalitarianism spirit to state woman as an autonomous and dignified personal and hasvalues. The portion of the man’s share who gets twice of the girl's actually is the maximum share (had al-aqsa) which should not exceed the maximum share of thesection, as well as the prohibition of giving a share of less than half of the male portionfor the girl. Allah’s Hudud in the form of legal limitation indicates the necessity ofequal sharing between men and women. So, the equality is the existence of the harmonyfrom the maximum share for men to the minimum share of women as the boundariesthat have been created by God.Keywords: Islamic Inheritance; Distributional Inheritance; Gender; Fiqh Muamalah;Equality.